Experimental and numerical investigation of effects of CNG and gasoline fuels on engine performance and emissions in a dual sequential spark ignition engine. Issue 18 (17th September 2018) - Yontar, Ahmet Alper; Doğu, Yahya
ABSTRACT: Compared to widening usage of CNG in commercial gasoline engines, insufficient but increasing number of studies have appeared in open literature during last decades while engine characteristics need to be quantified in exact numbers for each specific fuel converted engine. In this study, a dual sequential spark ignition engine (Honda L13A4 i-DSI) is tested separately either with gasoline or CNG at wide open throttle. This specific engine has unique features of dual sequential ignition with variable timing, asymmetrical combustion chamber, and diagonally positioned dual spark-plug. Thus, the engine led some important engine technologies of VTEC and VVT. Tests are performed by varying the engine speed from 1500 rpm to 4000 rpm with an increment of 500 rpm. The engine's maximum torque speed of 2800 rpm is also tested. For gasoline and CNG fuels, engine performance (brake torque, brake power, brake specific fuel consumption, brake mean effective pressure), emissions (O2, CO2, CO, HC, NOx, and lambda), and the exhaust gas temperature are evaluated. In addition, numerical engine analyses are performed by constructing a 1-D model for the entire test rig and the engine by using Ricardo-Wave software. In the 1-D engine model, same test parameters are analyzed, and same test outputs are calculated. Thus, the test and the 1-D engine model are employed to quantify the effects of gasoline and CNG fuels on the engine performance and emissions for a unique engine. In general, all test and model results show similar and close trends. Results for the tested commercial engine show that CNG operation decreases the brake torque (12.7%), the brake power (12.4%), the brake mean effective pressure (12.8%), the brake specific fuel consumption (16.5%), the CO2 emission (12.1%), the CO emission (89.7%). The HC emission for CNG is much lower than gasoline. The O2 emission for CNG is approximately 55.4% higher than gasoline. The NOx emission for CNG at high speeds is higher than gasoline. The variation percentages are the averages of the considered speed range from 1500 rpm to 4000 rpm.